Future Extensions to Passive Optical Access Networks - Radziwilowicz, Robert (2012)
Rapid changes in population distribution across Canada and the introduction of new telecommunication services to the consumer market have resulted in a number of significant challenges for existing network infrastructure. Fast growing populations in metropolitan regions require high density access networks to meet the growing need for bandwidth that results. Furthermore, new services such as high definition TV, online gaming and real-time video teleconferencing are becoming increasingly popular among consumers. These services require higher bandwidth to be available to end users. Changes in the Canadian economy will soon lead to a transition in Canadian industry from manufacturing to services and exploration of natural resources. This will create opportunities for new industrial development and growth in northern regions. Expanding industrialization towards northern Canada will require deployment of reliable telecommunication infrastructure. The combination of open source software, Linux operating system and Personal Computer (PC) based hardware platform is proposed to become the foundation for low cost and flexible technology that will provide transition towards all-optical infrastructures. An innovative prototype of a low-cost optical gigabit Ethernet switch is presented and its benchmark results are discussed. Scalability of the switch and its future applications in optical networks are studied. A prototype of a software based data encapsulation system was designed and implemented in a PC based platform, and its performance was evaluated using real data that was captured in commercial LAN. Semiconductor optical amplifiers (SOA) are studied as a building block in next generation switching devices for all-optical access networks. A prototype of an SOA-based low-cost optical switching device with implemented FPGA based controlling mechanism is presented and its characteristics are discussed. SOA is also studied as an energy efficient optical amplifier that can be deployed in end user facilities. The presented results provide proof of concept of a low cost flexible platform that can be used to design and build network devices to facilitate the transition of existing telecommunication networks towards next generation optical access infrastructure.